Gender and Students' Self-Compassion Level - Emma Dwi Ariyani; Dini Hadiani (Soshum: Jurnal Sosial dan Humaniora, 2019)
It is believed that self-compassion is beneficial for a human to survive in their environment. Self-compassion is the ability to entertain and care for oneself when suffering, failure and imperfection rather than self-criticism. This research attempts to find out the level of self-compassion in vocational higher education students and to explore the differences in terms of self-compassion between male and female students. Employing Neff's Self-Compassion Scale (short form) measurement tool, this study was conducted through a survey technique. The results show that female students had a slightly higher level of self-compassion than males. Regarding the significant elements of self-compassion which are self-kindness, common humanity, and mindfulness, it was found that there are differences in the dominant component of self-compassion between male and female students. This finding shows that female students were dominated by self-kindness rather than mindfulness and common humanity. It can be said that female students have more dominant ability to understand and accept themselves as well as to give tenderness. Whereas male students were dominated by common humanity rather than mindfulness and self-kindness. Male students have more dominant ability to perceive difficulties and problem which are part of human life, and these are things that everyone experiences and they always realize that they do not experience it by themselves. Based on the results of the study, it is expected that appropriate handling can be formulated to improve the students’ self-compassion.